2019
DOI: 10.1101/711978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collagen Production and Niche Engineering: A Novel Strategy for Cancer Cells to Survive Acidosis and Evolve

Abstract: Ductal Carcinoma in situ (DCIS) is an avascular disease characterized by profound acidosis. Premalignant cells within this niche must adapt to acidosis to survive and thrive. A component of this acidadaptation involves extracellular matrix remodeling leading to niche construction and remodeling.Using discovery proteomics, we identified that collagen producing enzyme PLODs are upregulated in acid-adapted breast cancer cells. Second harmonic generation microscopy showed significant collagen deposition within DCI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, over the past decade, it has become clear that tumours are a heterogeneous mixture of cells that differ in their genetic make-up and phenotypic behaviour (Merlo et al 2006;Gerlinger et al 2012;Basanta and Anderson 2013). As part of a recent study, currently in preparation for publication (Damaghi et al 2019), we observed significant heterogeneity in the distribution of matrix remodelling activity and acid adaptation among cancer cells in human breast cancer ducts ( Fig. 1).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, over the past decade, it has become clear that tumours are a heterogeneous mixture of cells that differ in their genetic make-up and phenotypic behaviour (Merlo et al 2006;Gerlinger et al 2012;Basanta and Anderson 2013). As part of a recent study, currently in preparation for publication (Damaghi et al 2019), we observed significant heterogeneity in the distribution of matrix remodelling activity and acid adaptation among cancer cells in human breast cancer ducts ( Fig. 1).…”
Section: Introductionmentioning
confidence: 62%
“…A pathologist reviewer scored the intensity of each stain on a scale from 0 to 3, where a 0 was considered negative, score 1 was weakly positive, score 2 was moderately positive, and score 3 was strongly positive. For further information, see Damaghi et al (2019).…”
Section: A1 Image Collection and Processingmentioning
confidence: 99%
“…However, over the past decade it has become clear that tumours are a heterogeneous mixture of cells that differ in their genetic makeup and phenotypic behaviour [38,29,7]. As part of a recent study, currently in preparation for publication [17], we observed significant heterogeneity in the distribution of matrix remodelling activity and acid adaptation amongst cancer cells in human breast cancer ducts ( Figure 1). Even along the invasive front the overlap of the regions of acid production and matrix remodelling is not complete ( Figure 1B).…”
Section: Abstract Tumour Invasion · Cooperation 1 Introductionmentioning
confidence: 77%
“…A pathologist reviewer scored the intensity of each stain on a scale from 0 to 3, where a 0 was considered negative, score 1 was weakly positive, score 2 was moderately positive and score 3 was strongly positive. For further information see [17].…”
Section: A1 Image Collection and Processingmentioning
confidence: 99%